A sulphonated oil for stabilisation of expansive soils. Issue Volume 20:Issued 11(2019) (2nd November 2019) - Soltani, Amin; Deng, An; Taheri, Abbas; Mirzababaei, Mehdi
ABSTRACT: The efficiency of a commercially manufactured sulphonated oil (SO) agent in treating a highly expansive soil was investigated through an extensive experimental program. A total of six SO to water mass concentrations, i.e. 0.25, 0.5, 0.75, 1, 1.25 and 2.5%, were examined. The test program included swell–load oedometer, unconfined compressive strength and cyclic wetting and drying tests. SO-stabilisation amended the soil's mechanical behaviour through improvements achieved in swelling and strength characteristics. The reduction in swelling potential and swelling pressure was dependent on SO concentration, while the effect of curing time was found to be insignificant. A similar dependency was concluded for the unconfined compressive strength and stiffness of the stabilised soil. Both dependencies suggested an SO concentration of 1.25% capable of yielding an optimal stabilisation scheme. Results of the cyclic wetting and drying tests indicated that the beneficiary effects of SO-stabilisation at optimum concentration, particularly in ameliorating the adverse effects of swell–shrink-related volume changes and to some extent increasing the strength, are strongly preserved under the influence of alternate wetting and drying.